Pengaruh Inflasi, Kurs, dan Harga Emas Terhadap Penyaluran Rahn (Studi Pada Bank Syariah Mandiri) - Soeharjoto Soekapdjo (ITB AAS INDONESIA Surakarta, 2021)
Indonesia, with a Muslim majority population, has made Islamic financial institutions develop rapidly. To meet community needs, Bank Syariah Mandiri developed alternative financing, by issuing gold pawn products (Rahn). Aims of this study is to determine factors that influence Rahn distribution. Used regression method with quarterly data in 2011-2018. Dependent variable is Rahn distribution and inflation, exchange rate and gold price as the independent variable. Result shown that inflation and gold price have a positive and significant effect on Rahn's distribution, while the exchange rate has a negative and significant effect on Rahn's distribution. For this reason, financial institutions can develop gold pawns by utilizing financial technology, and Government needs to maintain stable inflation and exchange rates in order to increase economic growth and income distribution.